Institutional factors of the development of innovative activity of Russian entrepreneurship ("Journal "U". Economy. Management. Finance.", 2023)
The article substantiates the activation of innovative activity as an important factor in the sustainable development of the economy. The level of innovative development of the Russian economy is influenced, first, by the development of innovative entrepreneurship. The article analyzes the problems and prospects of innovative activity of the business sector, as well as the creation of institutional conditions for its development in the context of digitalization of business processes.
Keywords: innovative development; innovation; innovative promotion; institutional factors; useful support